Increasing the Security Level in the Slovak Republic - Ladislav Simak (Communications - Scientific letters of the University of Zilina, 2008)
Increasing the security level in every country is a complicated process that affects all spheres of social life and requires a longer period of time. The improvement of the security system in the Slovak Republic has been taking place continuously since the country joined the European Union and NATO and has not been finished so far.